2020
DOI: 10.3390/ijerph17207599
|View full text |Cite
|
Sign up to set email alerts
|

Learning Abilities in a Population of Italian Healthy Preterm Children at the End of Primary School

Abstract: Background: Delays in learning skills have been extensively reported for very preterm children. However, few studies have examined academic achievement profiles in Italian preterm children as a function of their neonatal immaturity. Methods: A cross-sectional study was performed that included 82 healthy Italian children born very and extremely preterm (without major neurosensory outcomes; IQ ≥85). Children were evaluated for academic and neurocognitive performances at the second cycle of primary school. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…In recent decades, significant advances in perinatal and neonatal care have improved the survival rates of preterm infants, leading to increased interest in the cognitive developmental outcomes of this population. Studies on preterm children have often found reduced cognitive abilities and higher risks for developmental delay than in full-term populations, e.g., [ 2 , 3 , 4 , 5 ], although no delay was found in [ 6 ]. These difficulties include language deficits, e.g., [ 7 , 8 , 9 , 10 , 11 ] (but see [ 12 ] for a study failing to find deficits), related to different linguistic domains, such as the phonological [ 13 ], lexical [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and syntactic [ 13 , 21 , 22 ] domains.…”
Section: Introductionmentioning
confidence: 99%
“…In recent decades, significant advances in perinatal and neonatal care have improved the survival rates of preterm infants, leading to increased interest in the cognitive developmental outcomes of this population. Studies on preterm children have often found reduced cognitive abilities and higher risks for developmental delay than in full-term populations, e.g., [ 2 , 3 , 4 , 5 ], although no delay was found in [ 6 ]. These difficulties include language deficits, e.g., [ 7 , 8 , 9 , 10 , 11 ] (but see [ 12 ] for a study failing to find deficits), related to different linguistic domains, such as the phonological [ 13 ], lexical [ 5 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ], and syntactic [ 13 , 21 , 22 ] domains.…”
Section: Introductionmentioning
confidence: 99%
“…Some articles reveal that preterm participants show significant differences with respect to normative values and control groups. A higher incidence of learning impairments in very preterm children (gestational age < 33 weeks), compared to normative values, is described at the end of primary school [ 4 ]. Delays in very preterm samples (<32 weeks and very low birth weight < 1500 g) also persist into adulthood [ 5 ].…”
mentioning
confidence: 99%